2019
DOI: 10.1186/s12882-019-1377-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic length of morphologically-normal kidneys in children presented to a premier tertiary healthcare setting of Sri Lanka

Abstract: Background Accurate prediction of reference ranges of renal lengths facilitates clinical decision making. Currently a single renal-length-reference chart is used for both kidneys, which is solely based on the age of the child without adjusting for anthropometrics. Objective of the study is to assess the length of morphologically-normal kidneys ultrasonically and to build models to predict the renal lengths of children presenting at the Radiology Department of Lady Ridgeway Hospital fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Similar to other studies, we did not find statistically significant difference in renal length and volume between sex 2,8,14,15) and between the left and right kidneys of the same subject. 8,16) There fore, it is not necessary to concern about the child's sex and side of the kidney when examining the kidney size in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to other studies, we did not find statistically significant difference in renal length and volume between sex 2,8,14,15) and between the left and right kidneys of the same subject. 8,16) There fore, it is not necessary to concern about the child's sex and side of the kidney when examining the kidney size in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…A simple predictive formula that can easily estimate normal kidney length at the bedside would be highly useful in clinical practice. Several formulas for predicting the normal length of kidneys in children based on age and/or body height have been shown in previous reports (Supplementary Table S1) [ 3 6 , 10 13 ]. However, these formulas were relatively complicated for daily use at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also shows a significant relationship between kidney parameters and anthropometric measures. Some studies have shown that height correlates best with kidney length (23–27) while others revealed that weight is the best correlate with kidney length. In the present study, however, BSA correlates best with kidney length and volume, followed by weight and height.…”
Section: Discussionmentioning
confidence: 99%